Killer Folklore: Identity Issues in the True Crime Community - Barnes, Naomie (Ethnologies, 2019)
This article considers the development of identity within the True Crime Community (TCC) and examines the contagion theory of crime surrounding serial and mass murder within the United States. The TCC is an online Tumblr group that shares pictures, jokes, legends and other narratives surrounding such killers. TCC members are frequently blamed by outsiders for creating spaces where killers become celebrities which, in theory, creates more killers. Two issues arise out of contagion theory. The first is that modes of participation with crime representations and the production of texts around true crimes is shaped by contagion theory and vernacular debates about fandom. Second, contagion theory itself is open to critical cross disciplinary investigation for which folklorists, examining communities who participate in (re)producing true crime texts can offer valuable data, approaches and theory. Moreover, as folklorists working in rumour and contemporary legend have noted, we may have a role to play in interrupting crime cycles themselves.